The value perspective of technologically disrupted social dimension of a learning space - Andrea Annus; Kai Pata; Terje Väljataga; Halliki Põlda (Interaction Design and Architecture(s))
Technologically enhanced social dimension of a learning space is under researched, yet it plays an important role in supporting the learners. The aim of the study was to explore the values that underpin the construction of the social dimension of a learning space supporting adult education practices. Perceptions of higher education learners, learning facilitators, and educational technologists were collected in the form of group-interview workshops. Results indicated that disruptive technologies encourage the appearance of engagement, interactivity, effectiveness, empowerment and empathy in relation to the social dimension of a learning space. Findings suggest that disruptive technologies have the potential for the emergence of enhanced accessibility to learning, rise in learner autonomy and equity of the learning parties. However, questions regarding privacy, surveillance, trust and coercion of the social dimension might arise due to the technology integration.